The renewal of geography: an ongoing dispute - Barboza, João Paulo Morandi; Rondini, Carina Alexandra (Revista Ensino de Geografia (Recife), 2021)
Geography, as a discipline, is new compared to the others that belong to the school curriculum. As a science, it seeks to establish its paths of thought and object of study in the same constant in which the contemporary, globalized, technological world, constantly changing, seeks to establish its identity. Geography, which in its first incursions served as a strategic military means, found in the classic positivism some contribution for its development. Through the influence of the bourgeois class, it constituted a mold for its studies and asserts itself as a critical-social science, concerned with establishing relationships between man, as part of the society, and the geographical space that he occupies, in the search to understand, in a more complex, political, economic, social, as well as natural way, the world we inhabit. Aiming to understand the changes that Traditional Geography experienced until the establishment of the critical line of geographic thought, we seek, through a bibliographic review of classic and contemporary authors, to report the main demands that permeate this science. Therefore, this work synthesizes characteristics that permeate geographic science in its traditional aspect and its search for methodological renewal, of thinking as a science and of practice as a discipline, searching in the new Geography, or Critical Geography, ways and means to establish such a vision.